2017
DOI: 10.1371/journal.pone.0175521
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after antiretroviral therapy during the expansion of HIV services in Haiti

Abstract: BackgroundWe report patient outcomes after antiretroviral therapy (ART) initiation in a network of HIV facilities in Haiti, including temporal trends and differences across clinics, during the expansion of HIV services in the country.MethodsWe assessed outcomes at 12 months after ART initiation (baseline) using routinely collected data on adults (≥15 years) in 11 HIV facilities from July 2007-December 2013. Outcomes include death (ascertained from medical records), lost to follow-up (LTF) defined as no visit >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Worldwide, LTF rates for patients who have initiated ART treatment for at least one year range from 5 to 53% [ 1 , 3 – 10 ]. Patient characteristics associated with becoming LTF include being clinically ill, as measured by CD4 count or WHO symptom staging, low socioeconomic status, and concern for stigma, as well as structural factors such as transportation issues [ 3 , 7 – 10 , 45 47 ]. Several studies have reported high rates of re-engagement in care by patients who were previously labeled as LTF [ 3 , 4 , 7 , 8 , 11 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Worldwide, LTF rates for patients who have initiated ART treatment for at least one year range from 5 to 53% [ 1 , 3 – 10 ]. Patient characteristics associated with becoming LTF include being clinically ill, as measured by CD4 count or WHO symptom staging, low socioeconomic status, and concern for stigma, as well as structural factors such as transportation issues [ 3 , 7 – 10 , 45 47 ]. Several studies have reported high rates of re-engagement in care by patients who were previously labeled as LTF [ 3 , 4 , 7 , 8 , 11 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient characteristics associated with becoming LTF include being clinically ill, as measured by CD4 count or WHO symptom staging, low socioeconomic status, and concern for stigma, as well as structural factors such as transportation issues [ 3 , 7 – 10 , 45 47 ]. Several studies have reported high rates of re-engagement in care by patients who were previously labeled as LTF [ 3 , 4 , 7 , 8 , 11 , 45 ]. A study in South Africa found that up to 50% of patients who disengaged from care will re-engage within 3 years including care received at a hospital or emergency department visit [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations